Indigenous uses of some medicinal plants in Panchthar district, Nepal - Gautam, Tilak Prasad (Nepalese Journal of Biosciences, 2013)
Plants have been used as a source of medicine since ancient times. These medicines are cheaper and safe. According to WHO about 80% of the world’s population depends on traditional medicine for their primary health care. These traditional knowledge systems have started to disappear with the passage of time due to scarcity of written documents and relatively low income in these traditions. The present paper reports 87 species of medicinal plants from Panchthar district. Medicinal values of the plants are based on concepts and consideration of the local people. The further scientific studies need to evaluate the medicinal value of these plants. DOI: http://dx.doi.org/10.3126/njbs.v1i0.7479 Nepalese Journal of Biosciences 1: 125-130 (2011)